2018
DOI: 10.1016/j.jctube.2018.04.005
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic factors among TB and TB/DM comorbidity among patients on short course regimen within Nairobi and Kiambu counties in Kenya

Abstract: BackgroundThe double burden of diabetes mellitus (DM) and pulmonary tuberculosis (TB) is one of the global health challenges. Studies done in different parts of the world indicate that 12%-44% of TB disease is associated with DM. In Kenya TB-DM co-morbidity data is scarce and is not readily available. In this study we set to determine the difference in treatment outcomes among TB and TB/DM comorbidity patients and their respective clinical and socio-demographic characteristics.ObjectiveTo determine prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In Malaysia, employment status as a determinant of TB infection was showed that patients who were unemployed completed TB therapy at higher rates [ 35 ]. Our result was similar to a study in Kenya [ 41 ]. Productive age and employed status of individuals are risk factors for TB infection because of high mobility and the increased likelihood of being exposed to TB [ 35 , 42 ].…”
Section: Main Textsupporting
confidence: 93%
“…In Malaysia, employment status as a determinant of TB infection was showed that patients who were unemployed completed TB therapy at higher rates [ 35 ]. Our result was similar to a study in Kenya [ 41 ]. Productive age and employed status of individuals are risk factors for TB infection because of high mobility and the increased likelihood of being exposed to TB [ 35 , 42 ].…”
Section: Main Textsupporting
confidence: 93%
“…The positive relationship between excessive edible oil intake and DM is plausible as absorption of more lipids results in overweight, which has been shown to be a risk factor of DM 37 . In addition, in the present study, compared to Han ethnicity, people from the Buyi ethnic minority group were 1.37 (95% CI 0.98, 1.90) times more likely to develop DM, which might be due to the different lifestyle and cultural customs 38 . In our study, no gender difference was found, which is different from that in the previous studies in India 39 and Zambia 40 .…”
Section: Discussionmentioning
confidence: 47%
“…Tobacco use among adults was associated with being male (45,59,65). Several health factors were linked to tobacco use including hypertension (65), development of oral leukoplakia (34), pneumonia (82), increased odds esophageal cancer (77), ischemic stroke (83) and diabetes mellitus (70). In addition, tobacco use was associated with having had an injury in the last 12 months (81), emotional abuse (48) and psychological IPV (73).…”
Section: Studies Qualitatively Exploring Various Themes On Substance Use/sud (But Not Assessing Interventions)mentioning
confidence: 99%